Bibliometric Analysis on Ecotourism and Cultural Tourism Development - Judijanto, Loso; Respati, Rella Dwi; Kartini, Raden Asri; Difinubun, Yusron (Westscience Press, 2025)
This study presents a bibliometric analysis of ecotourism and cultural tourism research using data from Scopus and visualization through VOSviewer. The analysis identifies key research trends, influential scholars, and international collaborations that have shaped the academic landscape in these fields. The findings reveal that ecotourism research has evolved from a primary focus on environmental conservation and biodiversity to a broader integration of cultural heritage, economic sustainability, and digital transformation. Thematic clusters indicate a growing interest in climate change adaptation, stakeholder engagement, and smart tourism applications. Co-authorship and country collaboration networks demonstrate that the United States, China, Indonesia, and Malaysia lead in research output and international partnerships. However, some regions remain underrepresented in global research efforts. Challenges such as balancing conservation with tourism growth, ensuring economic viability, and fostering inclusive governance structures persist. The study underscores the need for interdisciplinary approaches, policy interventions, and technological innovations to enhance sustainable tourism development. Future research should focus on climate resilience, social entrepreneurship, and the role of digital technologies in responsible tourism practices.